REHABILITASI PENYALAHGUNAAN NARKOBA UNTUK REMAJA DI BANJARBARU - Machfuyana, Dhea Aghnia Putri; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Social Rehabilitation of narcotics abuse for adolescents In Banjarbaru is an institution which takes care and maintains adolescents patients who abuse narcotics to recover from their addiction. Social Rehabilitation Design is due to the large number of adolescents who use drugs and there are no special rehabilitation facilities for them yet. Issues raised in this report is how to create the design of social rehabilitation with outer space and inner space that can help the healing process. The method used to solve the issues using a healing environment. From these data, the healing environment concept emerged to create the design of outer space and inner space that can help in healing.